Pengembangan Media Pembelajaran Game Adventure dengan Konteks Budaya Melayu Maritim untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis pada Siswa SMP - Syahfiqah, Syarifah Iffa; Febrian, Febrian; Siregar, Nur Asma Riani (Universitas Maritim Raja Ali Haji, 2025)
Students' mathematical problem-solving skills remain a critical challenge in junior high school education, with only 5% of students able to solve problems effectively. This difficulty is compounded by abstract learning materials and a lack of engaging, culturally relevant learning media. This research project aims to develop an adventure game learning medium set in the context of Maritime Malay culture to enhance junior high school students' mathematical problem-solving abilities. The purpose of this study is to determine the validity, practicality, and effectiveness of the learning media. This study employed the ADDIE research method, consisting of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 35 eighth-grade students from SMP Negeri 1 Tanjungpinang. The instruments used were validation, practicality, and media effectiveness sheets. Data analysis techniques use both qualitative and quantitative methods. The material expert validation results showed an average assessment of 85.6%, indicating very valid criteria. The practicality results from the student-teacher trial showed 86.5% practicality, with very practical criteria. Furthermore, the product's effectiveness, measured using the N-Gain score, obtained a value of 0.61. Based on the data obtained, adventure games with a maritime Malay cultural context that improve mathematical problem-solving skills in junior high school students meet the criteria of validity, practicality, and effectiveness, making them suitable for use as learning media in the mathematics learning process.